Efeito de agentes clareadores de uso interno na resistência de união de pinos de fibra de vidro à dentina radicular - Ferreira, Josemar Martins (2012)
The aim of this study was to evaluate the effect of internal bleaching agents on fibreglass post bond strength to root dentine, seventy bovine teeth were divided into 7 experimental groups (n=10) varying the bleaching agent used: SpH- sodium perborate + 20%hydrogen peroxide; SpW- sodium perborate + distilled water; Cp37- 37%carbamide peroxide; Cp16- 16%carbamide peroxide; Cp10- 10%carbamide peroxide; H- 35%hydrogen peroxide; C- no bleaching agent (control). After bleaching protocols, posts were cemented with self-adhesive resin cement (RelyX U100) and roots were cross-sectioned to obtain two discs for each third. Posts were submitted to micropush-out test and bond strength values (MPa) were submitted to ANOVA in a split-plot arrangement and Tukey s test (p<0.05). Failure mode was evaluated under a confocal microscope. There was no significant difference between the control and groups with a bleaching agent. 16%carbamide peroxide (Cp16) resulted in higher bond strength value than sodium perborate + 20%hydrogen peroxide (SpH) on cervical third. The cervical third presented higher bond strength value compared to the apical third in the 10%carbamide peroxide (Cp10), 16%carbamide peroxide (Cp16) and sodium perborate + distilled water (SpW) and no significant difference in the other groups. The prevalence of adhesive cement-dentine failure was verified in all groups. The use of internal bleaching agents did not decrease fibreglass post bond strength to root dentin.